Activities and barriers in online professional development: A systematic literature review - Iswati Luluk; Hastuti Saptin Dwi Setyo (SHS Web of Conferences)
Despite the increased use of technology to facilitate English teachers’ professional development, there is a lack of comprehensive review of the employed activities and barriers. The current study aims to comprehensively look into the landscape of online professional development activities and the encountered barriers. Employing a systematic literature review approach, activity types and barriers of online professional development were identified. Through rigorous methodology, including database searches and inclusion criteria, 18 studies conducted in diverse global contexts were reviewed. The findings reveal four categorized professional development activities: structured learning, mentoring, informal learning, knowledge sharing, and social interaction. Barriers encompass attitudinal, physical, and structural factors such as negative attitudes, internet connectivity issues, and collaboration difficulties. The study concludes that effective communication, tailored solutions, and stakeholder collaboration are essential for overcoming the barriers of online professional development. The findings imply the crucial roles of stakeholders in enhancing online professional development for teachers. Future research should address the interplay of the barriers, their impacts, and innovative strategies.